Nanocasting hierarchical carbide-derived carbons in nanostructured opal assemblies for high-performance cathodes in lithium-sulfur batteries - Hoffmann, Claudia; Thieme, Soeren; Brueckner, Jan; Oschatz, Martin; Biemelt, Tim; Mondin, Giovanni; Althues, Holger; Kaskel, Stefan (ACS nano, 2014)
Silica nanospheres are used as templates for the generation of carbide-derived carbons with monodisperse spherical mesopores (d = 20-40 nm) and microporous walls. The nanocasting approach with a polycarbosilane precursor and subsequent pyrolysis, followed by silica template removal and chlorine treatment, results in carbide-derived carbons DUT-86 (DUT = Dresden University of Technology) with remarkable textural characteristics, monodisperse, spherical mesopores tunable in diameter, and very high pore volumes up to 5.0 cm3 g-1. Morphology replication allows these nanopores to be arranged in a nanostructured inverse opal-like structure. Specific surface areas are very high (2450 m2 g-1) due to the simultaneous presence of micropores. Testing DUT-86 samples as cathode materials in Li-S batteries reveals excellent performance, and tailoring of the pore size allows optimization of cell performance, especially the active center accessibility and sulfur utilization. The outstanding pore volumes allow sulfur loadings of 80 wt %, a value seldom achieved in composite cathodes, and initial capacities of 1165 mAh gsulfur-1 are reached. After 100 cycle capacities of 860 mAh gsulfur-1 are retained, rendering DUT-86 a high-performance sulfur host material.
CRIS-Team Scopus Importer:2023-03-20
Keywords: carbide-derived carbon; DUT-86; inverse opal; lithium-sulfur battery; small-Angle X-ray scattering